2017
DOI: 10.1016/j.stemcr.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Induction of Syncytiotrophoblast Layer II Cells from Trophoblast Stem Cells by Canonical Wnt Signaling Activation

Abstract: SummaryThe syncytiotrophoblast layer is the most critical and prominent tissue in placenta. SynT cells are differentiated from trophoblast stem cells (TSCs) during early embryogenesis. Mouse TSCs can spontaneously differentiate into cells of mixed lineages in vitro upon withdrawal of stemness-maintaining factors. However, differentiation into defined placental cell lineages remains challenging. We report here that canonical Wnt signaling activation robustly induces expression of SynT-II lineage-specific genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 57 publications
5
36
0
Order By: Relevance
“…We next asked whether p114RhoGEF-depleted TSCs can differentiate into labyrinthspecific trophoblast lineages. Induction of syncytiotrophoblast II cells (SynT-II) was achieved by GSK3β inhibition with CHIR9902 (Zhu et al, 2017). As expected, induction of differentiation resulted in downregulation of the TSC marker Cdx2 in control and p114RhoGEF-depleted cells; however, induction of SynB, a marker for SynT-II cells, was attenuated by p114RhoGEF depletion (Fig.…”
Section: P114rhogef Determines Trophoblast Actomyosin Organization Ansupporting
confidence: 54%
“…We next asked whether p114RhoGEF-depleted TSCs can differentiate into labyrinthspecific trophoblast lineages. Induction of syncytiotrophoblast II cells (SynT-II) was achieved by GSK3β inhibition with CHIR9902 (Zhu et al, 2017). As expected, induction of differentiation resulted in downregulation of the TSC marker Cdx2 in control and p114RhoGEF-depleted cells; however, induction of SynB, a marker for SynT-II cells, was attenuated by p114RhoGEF depletion (Fig.…”
Section: P114rhogef Determines Trophoblast Actomyosin Organization Ansupporting
confidence: 54%
“…Since culture conditions that favor mouse TS cell self-renewal or differentiation have been known for decades, these cells have provided the best studied in vitro models to investigate development of trophoblast lineages. Using two separate differentiation protocols, we induced mouse TS cells to either undergo conventional differentiation [4], or differentiate to preferentially form cells representative of the syncytiotrophoblast layer II lineage [21]. We found that Ovol2 mRNA levels robustly increased during both TS cell differentiation protocols.…”
Section: Discussionmentioning
confidence: 95%
“…TS cells were induced to differentiate by removal of MEF preconditioned media, FGF4, heparin, and activin A (differentiation media) [20]. To stimulate TS cell differentiation toward the syncytiotrophoblast II lineage (a sublineage of the labyrinth zone), cells were cultured in differentiation media, along with a GSK3β inhibitor, CHIR99021 (3 µM, Stemgent, Cambridge, MA, USA) [21]. Controls for TS cells exposed to CHIR99021 consisted of cells exposed to dimethyl sulfoxide (DMSO, 1:1000), which was the vehicle used to prepare CHIR99021.…”
Section: Cellsmentioning
confidence: 99%
“…To determine the function of 3-M genes in trophoblast migration, we utilized a previously established primary trophoblast stem cell (TSC) culture system (37). The TSCs can be maintained in TSC medium in the presence of FGF and heparin and induced to differentiate into trophoblast giant cells or syncytiotrophoblast layer II (SynT-II) cells by removing FGF and supplementing with retinoid acid (RA) or GSK inhibitor (CHIR) (38,39). Ccdc8 expression was undetectable in TSCs, but they started to express Ccdc8 upon differentiation ( Figure 6E).…”
Section: Resultsmentioning
confidence: 99%